ASSESSING OPERATIONAL CONSTRAINTS AND THEIR EFFECTS ON LABOR PRODUCTIVITY: EVIDENCE FROM LAUNDRY SMES IN TULUNGAGUNG, INDONESIA - Windu Suryajiwo; Aldi Widya Saputra; Anwar Fauzan Susanto; Bayu Prastyaning Aji Pradana (Jurnal Ilmiah Mahasiswa Akuntansi Universitas Tulungagung, 2024)
Laundry micro, small, and medium enterprises (MSMEs) play an important role in meeting the growing demand for time-efficient household services in Tulungagung, Indonesia. However, operational inefficiencies in laundry services may limit labor productivity, particularly during the ironing and packaging processes. Although productivity in MSMEs has been widely discussed, limited studies have specifically examined operational constraints and their implications for labor productivity in small-scale laundry businesses. This study aims to assess operational constraints affecting labor productivity in laundry MSMEs in Tulungagung, Indonesia, with particular emphasis on the packaging process. A descriptive research approach was employed using primary and secondary data. Primary data were obtained through direct field observations and interviews with laundry operators, while secondary data were used as supporting information. The analysis focused on the work process, human resource requirements, work systems, equipment utilization, and work-related fatigue. Productivity-related activities were classified into productive, effective, and non-value-adding activities, and descriptive analysis was applied to identify operational constraints and productivity-related inefficiencies. The findings indicate that inefficient workstation layout, repeated movements to retrieve garments and packaging materials, limited accessibility of supporting equipment, electricity interruptions, limited flexibility of ironing equipment, and physical fatigue are the main operational constraints. These conditions increase unnecessary movements and physical workload and may reduce the efficiency of working time. The study contributes practical insights for laundry MSMEs by emphasizing workstation reorganization, improved equipment accessibility, better work organization, and measures to minimize operational disruptions as potential strategies for improving labor productivity.